Mechanism Design and Simulation of Self-centering Center Rest Used in Grinding Machine - Zhao Yongqiang; Chai Xinning; Hou Hongling; Wang Yaofeng (Jixie chuandong)
The self-centering center rest is used in machining slender shaft parts such as lead screw,screw rotor and crankshaft. The machining precision of parts is affected directly by the clamping precision of self-centering center rest. The parametric mechanism model of self-centering center rest is established based on the mechanisms and theoretical mechanics. The load-carrying capability of self-centering rest is calculated by the long lead screw grinding for example. Combined with the parametric design and virtual prototype technology,then the motion simulation of the self-centering rest is analyzed. The simulation data and the theoretical calculation value are good consistency. Thus,a new method of structure design and topology optimization of self-centering center rest is provided.